Implementasi dan Evaluasi Protokol QUIC untuk Optimalisasi Kinerja Streaming Video Real-Time pada Jaringan 5G - Fauzan Prasetyo Eka Putra; Laili Romadona; Siti Fathiar Rohmah (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to analyze the effectiveness of QUIC protocol implementation in optimizing real-time video streaming performance on 5G networks. The method used is quantitative descriptive with a survey approach involving 150 5G network users and performance testing of QUIC protocol compared to TCP in various streaming scenarios. The results show that QUIC protocol provides significant improvements in latency (average 23% lower), throughput (15% higher), and packet loss recovery (40% faster) compared to traditional TCP. Quantitative data shows 78% of respondents experienced improved video streaming quality with QUIC implementation, while 85% rated connection stability as